When the drug of choice is a drug of confusion: embalming fluid use in inner city Hartford, CT. - Singer, Merrill; Mirhej, Greg; Shaw, Susan; Saleheen, Hassan; Vivian, James; Hastings, Erica; Rohena, Lucy; Jennings, DeShawn; Navarro, Juhem; Santelices, Claudia; Wu, Alan H B; Smith, Andrew; et al. (Journal of ethnicity in substance abuse, 2005)
This paper examines the use of a new illicit drug--embalming fluid mixtures--in Hartford, CT based on a recent assessment of drug consumption in an outreach-recruited sample of 242 not-in-treatment active drug users. Sociodemographic, drug use, and health and social problems of drug users who do and do not use embalming fluid mixture are presented, revealing some notable differences between these two groups of street drug users. Despite regular consumption, we report that embalming fluid mixture users are often uncertain about what is in this new drug, despite experiencing often powerful effects. Urine toxicology findings from a subsample of individuals who used embalming fluid mixtures in the last 48 hours, reveal the frequent presence of phencyclidine (PCP) as well as other drugs. The public health implications of this new wave of PCP use are assessed.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; African Continental Ancestry Group; Connecticut; Cross-Sectional Studies; Drug Contamination; Drug Interactions; Embalming; Ethnic Groups; European Continental Ancestry Group; Female; Formaldehyde; Health Surveys; Hispanic Americans; Humans; Incidence; Male; Phencyclidine; Phencyclidine Abuse; Risk Assessment; Street Drugs; Substance-Related Disorders; Urban Population